Grasslands Ecology Research Lab - Unidentified photographer (Colorado State University. Libraries, 1978)
The Grasslands Ecology Research Laboratory.
Not digitized by CSUL Digital Services.
Keywords: Grasslands Ecology Lab; Environmental Health Building; USDA Crops Research Laboratory